2013
DOI: 10.1002/jssc.201300576
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the HPLC enantioseparation of 3,3′-dibromo-5,5′-disubstituted-4,4′-bipyridines using immobilized polysaccharide-based chiral stationary phases

Abstract: The HPLC enantioseparation of nine atropisomeric 3,3',5,5'-tetrasubstituted-4,4'-bipyridines was performed in normal and polar organic (PO) phase modes using two immobilized polysaccharide-based chiral columns, namely, Chiralpak IA and Chiralpak IC. The separation of all racemic analytes, the effect of the chiral selector, and mobile phase (MP) composition on enantioseparation and the enantiomer elution order (EEO) were studied. The beneficial effect of nonstandard solvents, such as tetrahydrofuran (THF), dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Envisaging, for polysaccharide derivatives, a novel function other than resolution of racemic mixtures , in this paper we show that HPLC coupled with polysaccharide‐based CSPs as XB acceptors (XBAs) can serve as analytical means for detection of weak stereoselective XBs in solution. Chiral halogenated 4,4′‐bipyridines lacking perfluorination were used as XBD test compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Envisaging, for polysaccharide derivatives, a novel function other than resolution of racemic mixtures , in this paper we show that HPLC coupled with polysaccharide‐based CSPs as XB acceptors (XBAs) can serve as analytical means for detection of weak stereoselective XBs in solution. Chiral halogenated 4,4′‐bipyridines lacking perfluorination were used as XBD test compounds.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to know how the XB interaction works in LC chromatography, at both chiral and achiral levels, HBipys 1-33 ( Fig. 2A, Table 1) were designed, selected and synthesized through focused procedures [27][28][29][30][31]. Thus, firstly, the influence of the structure of CSP, halogen substitution pattern of the analytes and mobile phase (MP) polarity on the effectiveness of halogen-dependent enantioseparations were evaluated by means of the changes of the chromatographic responses upon structural variations.…”
Section: Introductionmentioning
confidence: 99%
“…Pure atropisomers can be obtained only by separating racemic mixtures of synthesized compounds and, for this purpose, HPLC methods can play a key role in the research plan development. In our previous work, the HPLC technique was used to enantioseparate atropisomeric 3,3′‐dibromo‐5,5′‐disubstituted‐4,4′‐bipyridines at multimilligram scale by using both cellulose‐ and amylose‐based chiral columns belonging to the series Chiralcel, Chiralpak, and Lux, which are known to efficiently enantioseparate molecular systems featuring a chiral axis as exclusive source of molecular dissymmetry . It was found that due to the high aromatic character of the analyzed 4,4′‐bipyridines, hydrophobic π–π interactions deeply contribute to the recognition mechanism both in normal‐phase liquid chromatography (NPLC) and polar organic solvent chromatography (POSC) elution modes.…”
Section: Introductionmentioning
confidence: 99%